Molecular characterization of clinical non-typhoidal Salmonella isolates shows high antimicrobial resistance burden in Jiangsu, China - Cao, Hui; Shen, Yun; Ma, Kai; Zheng, Dongyu; Xu, Yan; Qiao, Xin (Frontiers in Microbiology, 2025)
Non-typhoidal Salmonella (NTS) poses a significant global health burden due to its association with gastroenteritis and rising antimicrobial resistance (AMR). This study conducted a genomic analysis of 62 Salmonella isolates from outpatient cases in Jiangsu, China, to monitor the epidemiological characteristics of NTS, including genetic diversity, AMR profiles, and resistance transmission mechanisms 18 serovars and 21 sequence types (STs) were identified by whole genome sequencing, with S. enteritidis (27.42%) and S. typhimurium (19.35%) predominating. 61 resistance genes from ten different antimicrobial categories were found by genotypic AMR screening. 90.32% of isolates had β-lactam resistance genes, indicating a high frequency of extended-spectrum β-lactamases (ESBL). Serovar-dependent resistance patterns were highlighted by the most varied AMR profile (40/61 genes) found in S. typhimurium. The co-occurrence of genes for aminoglycoside resistance, sul2, and blaTEM indicated clustering driven by mobile genetic elements. A plasmid in a S. Stanley isolate harbored 12 AMR genes, which showed structural changes suggestive of horizontal gene transfer and active recombination. These findings underscore the role of plasmids in disseminating MDR and the urgent need for enhanced antimicrobial stewardship, food safety protocols, and One Health interventions to mitigate the spread of resistant Salmonella clones.